Reduction of Adolescent Idiopathic Scoliosis and Improved Z-Axis Alignment of the Entire Spine When Treating a Symptomatic Patient Using a Multidisciplinary Approach: A Case Report - Villa, Juan Jesus; Zhao, Zhiyang; Pan, Weicheng; Guo, Yongfei (Frontiers in Rehabilitation Sciences, 2022)
Background This study presents findings on improvements of both the X-axis and Z-axis posture in a young female with adolescent idiopathic, scoliosis suffering from pain complaints who was treated with a multidisciplinary approach. Case Presentation The 15-year-old patient reported low back pain for several months. Full spine radiographic assessment revealed a cervical kyphosis, forward head translation, a right ribcage translation, a left higher shoulder, and a dextroconvex lumbar scoliosis with a Cobb angle of 23°. The patient was treated with novel ASPINE Systems treatment protocols incorporating posture exercises, muscle balancing exercises, spinal 3D traction, and spinal manipulation. Results Assessment after 50 treatment sessions over 32 weeks revealed a dramatic improvement in postural distortions. The cervical kyphosis was reduced by 9° and was accompanied by a reduction in forward head posture, centering of the thoracic spine, leveling off her shoulders, and a reduction in the dextroconvex scoliosis by 10°. The lower back pain was relieved. Conclusion A reduction of postural distortions including idiopathic adolescent scoliosis resulted from a multidisciplinary approach utilizing ASPINE Systems.